2021
DOI: 10.3390/ani11010109
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sustainability in Cattle Silvopastoral Systems in the Mexican Tropics Using the SAFA Framework

Abstract: The sub-humid native rainforest in Yucatan is one of the most endangered in Mexico. Cattle production is one of the main causes of land use change and silvopastoral systems are a feasible alternative. This work compares the sustainable performance of silvopastoral (native and intensive) and monoculture cattle farms in the state of Yucatan using the Sustainability Assessment for Food and Agriculture (SAFA) framework. Questionnaires and semi-structured interviews were applied in 9 farms. Responses were fed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
11
0
3
Order By: Relevance
“…Overall, the results obtained in this study are consistent with previous publications, both qualitatively and quantitatively. We found that ISPSs show better indicators of sustainability than monoculture systems, which coincides with previous work in the region [49][50][51]. Furthermore, our data show a decrease in methane emissions, as measured by sniffer methodology [46] These results are also consistent with previous studies that have quantified methane emissions [25,31,52].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the results obtained in this study are consistent with previous publications, both qualitatively and quantitatively. We found that ISPSs show better indicators of sustainability than monoculture systems, which coincides with previous work in the region [49][50][51]. Furthermore, our data show a decrease in methane emissions, as measured by sniffer methodology [46] These results are also consistent with previous studies that have quantified methane emissions [25,31,52].…”
Section: Discussionsupporting
confidence: 92%
“…One of the key economic characteristics of SPS is increased biomass fluxes. Photosynthetic rates, nitrogen fixation, nutrient recycling and biomass production are all accelerated (Pérez-Lombardini et al, 2021). Biomass consumption by livestock removes a higher portion of the ecosystem's primary production.…”
Section: The Multifunctional Economy Of Silvopastoralist Systemsmentioning
confidence: 99%
“…This relies on diversification, market stability and developed safety nets, including risk management tools, access to financial and insurance and early warning systems. So far, participatory research on SPS in Latin America has shown a high level of economic resilience in both traditional SPS, such as Caívas in Brazil (Hanisch et al, 2019) and modern SPS (Pérez-Lombardini et al, 2021) analysed in both cases using the sustainability assessment of food and agriculture systems (SAFA) framework (FAO, 2014b).…”
Section: The Multifunctional Economy Of Silvopastoralist Systemsmentioning
confidence: 99%
“…According to the SAFA Guidelines, the Holistic Management theme considers the external effects of the farm activities in accounting and decision making, while the Accountability theme relates to disclosure and availability of correct and complete information about all aspects of the farm's performance (FAO, 2014). Similarly, other SAFA-based studies found a poor performance in terms of Accountability and Holistic Management of smallholder farms in developing countries and elsewhere (Landert et al, 2017;Pérez-Lombardini et al, 2021;Schader et al, 2016). A study of noncertified and conventional smallholder coffee farmers in Ethiopia, for example, found that they did not use formal farm monitoring methods (Winter et al, 2020).…”
Section: Farm Management and Accountabilitymentioning
confidence: 99%
“…Organic agriculture is usually associated with production diversification e.g. in crops through intercropping and crop rotation, which reduces vulnerability to different economic and environmental shocks (Pérez-Lombardini et al, 2021;Singh & Maharjan, 2017). In general, diversification is positively associated with risk reduction and wealth accumulation (Barrett et al, 2001;Davis et al, 2017), but these benefits can be undermined by yield losses, which can affect farm income and consequently, economic resilience.…”
Section: Farm Enterprisesmentioning
confidence: 99%